The Modern Methods of Animal's Slaughtering in Malaysia: An Islamic Perspective - Faizah Bt Md. Yusof (Universiti Sains Islam Malaysia, 2022)
The purpose of this academic writing is to study how far the halalness and the legality of modem methods of animal slaughtering as practiced in Malaysia, as it will help to increase the public's confidence towards halal meat sold in the Malaysian market. This study has identified, the stunning system of animals prior to slaughter are carried out in Malaysia nowadays are different with the original system that introduced by the western countries. In order to accomplish this study, past researches, library references and interview have been utilized as sources to obtain related information. The outcome of the study has shown that the modem method of animal's slaughtering is permissible in Hukum Syarak and the manufacturers in Malaysia follow the certain standard required by the authority. The Malaysian Islamic Development Department (JAKIM) has played an important role in its halal certification effort. And finally, the research concludes with the discussion on the Trade Description Act 1972 that use in Malaysia is not ascertains enough on the halalness of the product. To extinguish the confusion and ambiguity among Muslim consumers thus, the government should emerge an explicit halal act in meat production in Malaysia.